2008
DOI: 10.3844/ajbbsp.2008.208.217
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Mitochondrial Dysfunction in Autism and Implications for Treatment

Abstract: Classical mitochondrial diseases occur in a subset of individuals with autism and are usually caused by genetic anomalies or mitochondrial respiratory pathway deficits. However, in many cases of autism, there is evidence of mitochondrial dysfunction (MtD) without the classic features associated with mitochondrial disease. MtD appears to be more common in autism and presents with less severe signs and symptoms. It is not associated with discernable mitochondrial pathology in muscle biopsy specimens despite obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 109 publications
1
47
0
2
Order By: Relevance
“…Inhibition of aerobic respiration leads to â-oxidation impairment and decreases cellular energy level that lead to increase in anaerobic respiration. So, lactate level increases 9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inhibition of aerobic respiration leads to â-oxidation impairment and decreases cellular energy level that lead to increase in anaerobic respiration. So, lactate level increases 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In mitochondrial dysfunction ATP level decreases that impairs urea cycle. So ammonia level in blood increases 9 . Increased ammonia level in autism spetrum disorder children may lead to toxicity and ATP depletion in brain 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a major component of non-specific immune response in host cells exposed to exogenous double-stranded RNA. This inturn precipitates the phosphorylation of eukaryotic initiation factor 2a (eIF2-a), a gene known to hinder viral replication, by blocking protein synthesis (6,10). Romark first showed that chronic HCV patients were cured with nita-…”
Section: Discussionmentioning
confidence: 99%